Analysis of Fishing Business Using Gill Net Fishing Gear in Bogak Village, Tanjung Tiram District, Batu Bara Regency, North Sumatra Province - Hendrik, Hendrik; Yanti, Chicka Willy; Silitonga, Rahmi Julita Hotmaria Br. (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
The majority of the population of Bogak Village works as fishermen, with 76% of them involved in fishing. The dominant fishing gear used is gill nets, with a total of 500 units. This study was conducted in Bogak Village in 2023 to determine the investment spent by fishermen, the total costs, income, and profits they obtain, and to analyze the feasibility of fishing efforts using gill nets. This research method is a survey method with 21 fishermen as respondents. The results indicate two criteria for the type of fishing business: using 5 GT and 10 GT fleets. The investment for a 5 GT fleet is IDR 78,991,375.00, while a 10 GT fleet costs IDR 232,150,972.22. The total cost of the 5 GT fleet is IDR 525,031,138.89 / year, and the 10 GT fleet is IDR 776,833,809.52 / year. The income of the 5 GT fleet is IDR 581,760,000.00/year, and the 10 GT fleet is IDR 904,106,666.67/year. The profit of the 5 GT fleet is IDR56,728,861.11/year, and the 10 GT fleet is IDR127,272,857.14/year. Based on the feasibility analysis of the gillnet fishing business, both fleet sizes (5 GT and 10 GT) have proven to be profitable with an R/C value above 1. This indicates that the company is feasible to continue and develop. Overall, investing in a larger fleet provides more promising economic prospects for fishermen